PENINGKATAN MOTIVASI BELAJAR SISWA KELAS VII SMPN 4 TAMBANG PADA MATERI SUHU DAN KALOR MENGGUNAKAN MEDIA PEMBELAJARAN POSTER - Mulyani Hafizhah; Zuhdi Ma’aruf; M. Rahmad M. Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research aims to describe the effect of using poster media on students’ learning motivation and to find out the differences in learning motivation between experimental class students and contol class students. The methode used in this research is quasi-experiment by using Nonquivalent Control Group Design. The subject in this research were seventh grade students of SMPN 4 Tambang which consisted of 60 students and were divided into two classes, they were experimental class and control class. The research instrument used was the ARCS motivation questionnaire. This research was implemented on odd semester 2021/2022. The data in this research are scores of learning motivation before and after applying poster learning media which was analyzed descriptively and inferentially. Descriptively, the data was analyzed by normalizing gain (N-gain) to see the increasing of learning motivation of students. Inferentially, the data was analyzed by using independent sample t-test to see the difference of student’s learning motivation. The result of this research showed that the increasing of students learning motivation at experimental class is in the middle category with N-gain 0,43. While the control class is in the low category with N-gain 0,27. Inferentially showed that there was a difference It can be concluded that there is a differences of a learning motivation between group using a poster learning media and the group without poster medi. So it can be conclude that the poster media is worth to be used in order to increas student’s learning motivation in class VII SMPN 4 Tamabang on temperature and heat material.Key Words: Poster Media, Learning Motivation, Temperature and Heat